Nutraceutical supplements from subtropical fruits - Singh, Akath; Singh, N Samarendra; Gupta, A K; Singh, Abha (Indian Horticulture, 2026)
Nutraceuticals, derived from food sources with health-promoting properties, are increasingly recognized as essential components of preventive healthcare and functional foods. The growing prevalence of chronic diseases and rising consumer demand for natural remedies have accelerated the global expansion of the nutraceutical market. Subtropical fruits such as mango, jamun, guava,bael, aonla, and wood apple serve as valuable sources of bioactive compounds, including polyphenols, flavonoids, carotenoids, and glycosides, with well documented therapeutic benefits. Advanced processing technologies like infrared drying and nano-encapsulation further enhance the bioavailability, stability, and shelf life of fruit-derived products. Nutraceutical-enriched food supplementsdeveloped from subtropical fruits at ICAR-CISH Lucknow are briefly highlighted in this article, emphasizing their role in nutrition and health.